Factors influencing the intention to give zakāt on employment income: Evidence from the Kingdom of Saudi Arabia - Aziz Ur Rehman; Ejaz Aslam; Anam Iqbal (Islamic Economic Studies (IES), 2021)
Purpose This study aims to apply the extended theory of planned behaviour (ETPB) to investigate the factors influencing the intention to give zakāt on employment income. Design/methodology/approach This study draws the required data through a survey in three main cities Makkah, Medina and Jeddah in Kingdom of Saudi Arabia (KSA). The final data sample is consisting of 650 useable questionnaires to analyse the objective of this study. Findings The study finds that moral norm, injunctive norm, descriptive norm and past behaviour have a significant influence on the intention to pay zakāt on employment income. The perceived behavioural control and attitude have a negative and weak impact on the intention to give zakāt on income. Research limitations/implications The findings of this study can be useful for the policymakers and regulators to enhance peoples' awareness to give zakāt to eradicate poverty and inequality in Muslim societies. zakāt is for the deprived people, so the consequences of this study might help to improve their liveability. Originality/value This study is unique because it identified the behavioural factors that affect the peoples' intention to give zakāt in KSA have yet to be profoundly explored in the literature. This study has gathered primary data and applied the ETPB to identify the factors influencing the zakāt compliance behaviour in KSA.
Keywords: D21; O16; G20; 330; Intention; Norms; Saudi Arabia; Theory of planned behaviour; Zakāt